Pharmaceutical, Analytical and Chromatographic Evaluation of Ark Tail: An Ayurvedic Oil Formulation (International Journal of Ayurveda and Pharma Research, 2025)
Arka Taila, a classical Ayurvedic medicated oil formulation described in Sharangadhara Samhita, is traditionally used for the management of skin disorders such as Vicharchika (eczema), Pama (scabies), and Kacchu (itching). Despite its therapeutic significance, limited scientific research has been conducted on its pharmaceutical and analytical characterization. Materials and Methods: Arka Taila was prepared using the Sneha Kalpana method with a standard ratio of 1:4:16 (Kalka:Sneha:Drava) incorporating Haridra Kalka (Curcuma longa), Murchita Sarshapa Taila (processed mustard oil), and Arka Patra Swarasa (Calotropis juice). Murchana Sanskara was performed as per classical texts to enhance the oil base. Pharmaceutical evaluation included observation of Sneha Siddhi Lakshanas. Organoleptic parameters, physicochemical tests (including refractive index, acid value, saponification value, iodine value, pH, etc.), and HPTLC profiling were carried out as per the standards of the Ayurvedic Pharmacopoeia of India. Results and Discussion: The formulation exhibited classical Sneha Siddhi Lakshanas confirming proper processing. Physicochemical parameters were within acceptable limits: refractive index (1.46729), acid value (1.245), iodine value (116.9), and peroxide value (1.02), indicating stability and purity. HPTLC profiling revealed multiple distinct phytochemical bands in Arka Taila that were absent in both Amurchit and Murchit mustard oil, validating the successful infusion of herbal and distillate bioactive components. Conclusion: The study validates the traditional preparation and pharmacological integrity of Arka Taila through modern scientific parameters. Its pharmaceutical stability, phytochemical richness, and favourable physicochemical profile support its continued therapeutic use and pave the way for further clinical and pharmacological investigations in dermatological applications.